PERCEPTION OF TEACHERS ABOUT THE LEARNING PROCESS IN NURSING ADMINISTRATION - Cristiano Caveião; Ivete Palmira Sanson Zagonel; Izabel Cristina Meister Coelho; Aida Maris Peres; Juliana Helena Montezeli (Universidade Federal do Paraná, 2015)
This study aimed to identify the Nursing Administration learning process in daily education from the perspective of faculty members teaching this subject. Exploratory and descriptive study with a qualitative approach, undertaken between July and September 2012, involving faculty members from five private and six public higher education institutions in the South of Brazil. The content analysis of 25 faculty members' interviews revealed two categories: learning process in daily Nursing Administration education and assessment of the Nursing Administration learning process. The results indicate that compartmentalized curricula continue to exist, that the course lacks diverse practical scenario and specific teacher training, while the use of active strategies/methods appears. The study formulates recommendations for the teaching institutions and the faculty members in order to improve the actions in the Nursing Administration learning process.